(untitled) (The Review of Diabetic Studies, 2025)
Background: Saudi Arabia’s Vision 2030 has introduced an ambitious national agenda to restructure the healthcare system through the Health Sector Transformation Program (HSTP). This transformation seeks to establish a sustainable, efficient, and patient-centered model of care that emphasizes accessibility, quality, and innovation. Despite extensive policy reforms, there remains limited consolidated evidence on how effectively these initiatives have been implemented and the extent of their measurable outcomes across the Saudi healthcare landscape. Aim: This systematic review aims to critically evaluate the implementation and outcomes of healthcare transformation initiatives under Saudi Vision 2030, focusing on governance, financing, service delivery, digital innovation, and workforce development. Method: Following PRISMA 2020 guidelines, a multi-database search was conducted across PubMed, Scopus, Web of Science, CINAHL, EconLit, and official Saudi Ministry of Health (MoH) and HSTP portals for studies published between 2016 and 2025. From 1,448 identified records, ten primary studies met the inclusion criteria. Quality appraisal was performed using JBI, ROBINS-I, and AMSTAR-2 tools, and a thematic synthesis was conducted. Results: Five major themes emerged: (1) governance and policy implementation, (2) healthcare financing and privatization, (3) model of care and service delivery, (4) digital health and innovation, and (5) workforce and capacity building. The findings indicate notable progress in policy integration, accountability, and technological advancement, though disparities persist in financing equity, workforce readiness, and regional implementation consistency. Conclusion: Vision 2030’s reforms have established a robust framework for sustainable healthcare transformation in Saudi Arabia. Continued monitoring, policy adaptability, and investment in human capital and digital integration are essential for long-term success.